Defining and Designing Mixed Research Synthesis Studies - Sandelowski, Margarete (2006)
Mixed research synthesis is the latest addition to the repertoires of mixed methods research and systematic review. Mixed research synthesis requires that the problems generated by the methodological diversity within and between qualitative and quantitative studies be resolved. Three basic research designs accommodate this diversity, including the segregated, integrated, and contingent designs. Much work remains to be done before mixed research synthesis can secure its place in the repertoires of mixed methods research and systematic review, but the effort is well worth it as it has the potential to enhance both the significance and utility for practice of the many qualitative and quantitative studies constituting shared domains of research.